Review on Health Care Monitoring System - Pawar, Rahul; MM, Sardeshmukh; Shinde, Sagar (International Journal of Computer Sciences and Engineering, 2019)
The healthcare monitoring systems have drawn considerable attentions of the researchers. The prime goal was to develop a reliable patient monitoring system so that the healthcare professionals can monitor their patients, who are either hospitalized or executing their normal daily life activities. In this work we present a mobile device based wireless healthcare monitoring system that can provide real time online information about physiological conditions of a patient. Our proposed system is designed to measure and monitor important physiological data of a patient in order to accurately describe the status of her/his health and fitness. By using the information contained in the text or e-mail message the healthcare professional can provide necessary medical advising. The system mainly consists of sensors (i.e. temperature sensor, gyroscope, accelerometer), location locker (i.e. GPS), microcontroller (i.e. Node MCU), and software (i.e. Embedded C). The patients temperature, no. of steps he/she walks, location, displayed, and stored by our system. Along with above mention parameters, android app will display timing and amount for drinking water and alert about same.